An Innovative Approach to Data Analysis in The Field of Energy Consumption and Energy Conversion Efficiency in Vehicle Drive Systems – The Impact of Operational and Utility Factors - Piotr WRÓBLEWSKI (Communications of International Proceedings, 2021)
Nowadays, the number of used and manufactured vehicles with electric BEV (Battery Electric Vehicle) or hybrid PHEV (Plug-in Hybrid Electric Vehicle) drive is rapidly increasing due to the generally accepted global trend of reducing harmful substances emitted to the environment. There are many operational and utility factors that determine the economical use of selected systems of the energy supply and the drive system of vehicles. The driving conditions reflecting the profile of speed, acceleration and braking influence to a large extent the legitimacy of using selected solutions of the drive system in a given operating territory. Additional factors are the reliability parameters of selected components introduced in the overall chain of energy storage, transmission and processing. It largely determines the quality and technology of the production of individual units of the operating system. The paper presents the results of simulation tests concerning the percentage values ​​of the loss of capacity batteries and energy consumption depending on the frequency and acceleration values ​​for various timetables. The paper presents a mathematical model for simplified prediction of the loss of essential capacities with the energy source, taking into account many indirect factors. Factors influencing the increase in energy demand in the storage tanks and their operating conditions were assumed. Occurring short-term extreme operating conditions significantly deteriorate the conditions of use, which affects the reliability of individual components, mainly the energy absorbing and transmitting unit. The detailed results contained in the work allow to assess the scale of the impact of these factors on the total energy balance of the vehicle in various conditions, taking into account the specific conditions of its operation.
Keywords: Battery; Charging; Control; Electricity Management System.